Envolvimento dopaminérgico na modulação da resposta de estresse em peixes-zebra (Danio rerio) - Idalencio, Renan (2019)
The dopaminergic system is the subject of numerous researches due to its complexity and to have numerous pathways and receptors in the central nervous system. The release of catecholamines such as dopamine and norepinephrine, are dependent on the presence of tyrosine hydroxylase, which converts L-tyrosine to L-DOPA / levodopa and later into dopamine by dopa decarboxylase. Finally, dopamine is converted to norepinephrine by dopamine β-hydroxylase. On the other hand, L-tyrosine analogues such as a-methyl-para-tyrosine are potent competitive inhibitors of tyrosine hydroxylase, inhibiting the production of catecholamines. It should be noted that dopamine is responsible for innumerable functions such as locomotion, cognition, emotion and neuroendocrine functions. In this context, our objective was to investigate the participation of the dopaminergic pathway on the neuroendocrine axis of stress in zebrafish. We have shown, based on the results of the two articles described, that there is an intimate relationship between catecholamine’s and glucocorticoids in neuroendocrine stress responses. In the first article, we showed that a-methyl-para-tyrosine was able to block the stress axis in adult zebrafish after a stressor event. And in the second article after blocking the dopaminergic pathway with a-methyl-para-tyrosine and subsequent levodopa supplementation, we strongly suggest that dopamine is related to the balance of stress response and norepinephrine to decrease this response.